Dampak Implementasi Prinsip Mempersulit Perceraian Terhadap Pemenuhan Hak Perempuan - Kharisma, Bintang Ulya (Green Publisher Indonesia, 2025)
The principle of making divorce difficult in the Indonesian family law system aims to maintain the integrity of the household. However, the implementation of this principle often causes injustice, especially to women. This paper aims to examine the implementation of this principle in judicial practice and its impact on the fulfillment of women's rights, both legally and socially. By using normative and sociological juridical approaches, as well as qualitative analysis techniques, this study shows that the principle of making divorce difficult can hinder women's access to justice, especially in cases of domestic violence, economic rights, and social rights. Therefore, a critical evaluation and reformulation of family law policy is needed to make it more gender-equitable.